Caffeine-inducible gene switches controlling experimental diabetes - Daniel Bojar (Nature Portfolio, 2018)
Control of transgene expression should ideally be easy and with minimal side effects. Here the authors present a synthetic biology-based approach in which the caffeine in coffee regulates a genetic circuit controlling glucagon-like peptide 1 expression in diabetic mice.